KONSUMEN RAMAH LINGKUNGAN: PERILAKU KONSUMSI HIJAU CIVITAS ACADEMICA UNIVERSITAS DIPONEGORO - Maria Ursula Mai Cruz; Bulan Prabawani (Universitas Diponegoro, 2017)
Rapid economy growth encourages natural resources consumption and exploitation causing environmental degradation excessively. Environmental degradation is driven by consumption habits of private household leads to the environmental deterioration such global warming, ozone depletion, and even threats to human’s health. Expanding more sustainable consumption and production doesn’t only depend on environmental technologies innovation and social changes, but also changes of consumption patterns and behavior of consumers. The aim of this study is showing the influence factors of green consumption behaviors. Besides, it describes consumption behaviors done by consumers hence it becomes market segmentation. As an effort to respond on the research problems and goals, the research used a study case method and data collection from in-depth interviews, observation, and documentation of the civitas academica of Universitas Diponegoro Semarang. The findings showed formal education is the most influenced demographic factor. Lifestyle, values, and benefits of the green product are the most influenced psychographic factors of the consumer. The environmental attitude is affected by environmental awareness, promotion of the firms, media, word of mouth communication, and also reference group. The green consumption behaviors involved efficiency of energy using, reducing plastics, and purchasing green products. The findings suggested business institution to make green product innovation and to increase consumer environmental knowledge by using education, media, advertisement, WOM communication, and reference group.